Bridging the Financial Inclusion Gap Through Fintech: Evidence from Literature on Banking Digitalization and Community Impact - Ayu Amrita , Nyoman Dwika (KRIEZ ACADEMY : Journal of development and community service, 2024)
This literature-based paper analyzes how fintech-driven banking digitalization contributes to narrowing the pervasive financial inclusion gap, particularly among underserved populations. It draws from a synthesis of global studies on neobanks, agency banking, and digital identification (ID) integration to critically assess how technology fundamentally transforms access to finance. The paper systematically examines the operational models, observed outcomes, and critical success factors of these initiatives. Furthermore, it discusses strategic policy implications for fostering inclusive innovation, emphasizing that the balance between regulatory oversight and technological advancement is crucial for sustainable impact. This review contributes to the discourse on development finance by providing a comprehensive, evidence-based understanding of the mechanisms through which fintech can be leveraged to create more equitable and resilient financial ecosystems in emerging markets.